The Pox Lover An Activist's Decade in New York and Paris - d'Adesky, Anne-christine (The University of Wisconsin Press, 2017)
The Pox Lover is a personal history of the turbulent 1990s in New York City and Paris by a pioneering American AIDS journalist, lesbian activist, and daughter of French-Haitian elites. In an account that is by turns searing, hectic, and funny, Anne-christine d'Adesky remembers "the poxed generation" of AIDS-their lives, their battles, and their determination to find love and make art in the heartbreaking years before lifesaving protease drugs arrived.